Frequency of Thyroid Disorders in a Tertiary Care Hospital of Lahore, Pakistan - Muhammad Zubair; Zaineb Hameed; Hira tahir; Saira Farhat; Tahseen Kazmi; Noor Shahid (Shalamar Medical & Dental College, Lahore, Pakistan, 2023)
Background: Two powerful hormones are produced by thyroid gland, thyroxine (T4) and triiodothyronine (T3). These hormones control all metabolic processes and influence oxygen consumption in nearly all tissues of the body. Objective: To determine the frequency of various thyroid disorders and association of thyroid disorders with age. Methods: A retrospective descriptive study was conducted at Chemical Pathology and Immunology department, of a tertiary care hospital Lahore, Pakistan from October 2020 to April 2021. Reports of thyroid function test (TFT) of patients from 1st October 2020 to 31st December 2020 were included. Thyroid profile includes three parameters i.e. thyroid stimulating hormone (TSH), free T3 and free T4. Frequency of thyroid disorders was determined according to age and sex. Chi-square was used to determine association between age-groups and vice versa.   Results: Among 239 thyroid profiles of patients, 146 (61%) were found to be within normal range, whereas thyroid profile of 93 (38.9%) patients was disturbed, and they had various thyroid disorders. Frequency of thyroid disorders were significantly associated with age (p value=0.03). Among the patients with disturbed thyroid profile TSH was low in 14 (15.1%) patients and high in 57 (61.30%). Conclusion: More than one-third of the suspected patients were found to have thyroid disorder. Thyroid disorders were significantly associated with age. Thyroid dysfunction was more common among female patients and presentation of hypothyroidism was more common among after 30 years of age